Two new species of riparian hoppers (Amphipoda, Talitridae) from Trat and Samut Prakan provinces, Thailand - Anotai Suklom; Tosaphol Saetung Keetapithchayakul; Azman Abdul Rahim; Koraon Wongkamhaeng (ZooKeys)
Floresorchestia has been recorded from the South African coast throughout the tropical Indo-Pacific and Caribbean seas. Platorchestia exhibits a distribution along the coastlines of the Atlantic Ocean and has been documented in the Baltic and Mediterranean seas, North America, Bermuda, and South Africa; however, it has not been recorded in Southeast Asia. This study presents the discovery of two new species of Floresorchestia and Platorchestia (Crustacea: Amphipoda) from a small creek bank in Trat and Bang Pu, Samut Prakan Province, respectively. These new species, classified as riparian hoppers, significantly contribute to the existing biodiversity in Southeast Asia. Floresorchestia trisetosa sp. nov. can be distinguished by left mandible lacinia mobilis 4-dentate; gnathopod 2 palm reaching approximately 34%; telson as broad as long, with three robust setae per lobe. Platorchestia aquaticus sp. nov. can be distinguished by gnathopod 1 subchelate, cuspidactylate, gnathopod 2 palm reaching approximately 35%; telson with three marginal robust setae, and three apical robust setae per lobe.